Mental toughness for young athletes : the blueprint on how to push past failure, remain competitive, and bring your a-game on the field - Hardy, Paul ([Place of publication not identified] : Ippoceronte Publishing, 2022)
Throughout this book, you will hear about the inspirational stories of the world's greatest sportsmen and women and how they were able to develop mental toughness and break world records. You will also receive practical tips and strategies on how to rewire your mind for success, create and visualize your goals, and handle failure and rejection.
Introduction -- Chapter 1. The cost of being a high-performing athlete -- Chapter 2. Bring your a-game -- Chapter 3. Making sacrifices and finding the right balance -- Chapter 4. Family culture -- Chapter 5. Setting and achieving goals -- Chapter 6. Focus on what you can control -- Chapter 7. Rewire how you think -- Chapter 8. Build Confidence in your skills -- Chapter 9. How to Approach a training session and competition -- Chapter 10. Dealing with success and failure -- Conclusion -- Printable Resources -- References.
Includes bibliographical references.
Keywords: ATHLETE